A companion to the anthropology of American Indians - Biolsi, Thomas 1952- (Blackwell companions to anthropology, 2008)
The status of American Indians has been rooted in a view of Indians as members of indigenous polities with distinct cultures. Often, these cultures have been characterized by dominant colonial authorities as "savage" or "primitive," and it is the discipline of anthropology that, willingly and wittingly or not, helped to make the idea of "the primitive" into a social reality. Consequently, the "tribal slot" inhabited by American Indian-with both its benefits and its oppressions-is difficult to imagine without the discipline of anthropology. A Companion to the Anthropology of American Indians contains 26 original contributions by leading scholars who work actively as researchers in American Indian communities, or on the topic of American Indians. The book summarizes the state of anthropological knowledge of Indian peoples, as well as the history that got us to this point. Treated here is the full range of anthropological interest in American Indians: from ecological and political-economic questions to topics concerning religion, language, and expressive culture. Each chapter provides definitive coverage of its topic while situating ethnographic and ethnohistorical data in a broader framework. This framework includes the linked histories of American Indians and anthropology, the role of continued native resistance in changing both the situation of Indian people and the content of anthropology, and the potential roles of anthropology in an anti-colonial project that speaks to the pressing concerns of contemporary Indians.